RNA editing by ADAR1 regulates innate and antiviral immune functions in primary macrophages. Issue 1 (December 2017) - Pujantell, Maria; Riveira-Muñoz, Eva; Badia, Roger; Castellví, Marc; Garcia-Vidal, Edurne; Sirera, Guillem; Puig, Teresa; Ramirez, Cristina; Clotet, Bonaventura; Esté, José; Ballana, Ester
Abstract ADAR1-dependent A-to-I editing has recently been recognized as a key process for marking dsRNA as self, therefore, preventing innate immune activation and affecting the development and resolution of immune-mediated diseases and infections. Here, we have determined the role of ADAR1 as a regulator of innate immune activation and modifier of viral susceptibility in primary myeloid and lymphoid cells. We show that ADAR1 knockdown significantly enhanced interferon, cytokine and chemokine production in primary macrophages that function as antiviral paracrine factors, rendering them resistant to HIV-1 infection. ADAR1 knockdown induced deregulation of the RLRs-MAVS signaling pathway, by increasing MDA5, RIG-I, IRF7 and phospho-STAT1 expression, an effect that was partially rescued by pharmacological blockade of the pathway. In summary, our results demonstrate a role of ADAR1 in regulating innate immune function in primary macrophages, suggesting that macrophages may play an essential role in disease associated to ADAR1 dysfunction. We also show that viral inhibition is exclusively dependent on innate immune activation consequence of ADAR1 knockdown, pointing towards ADAR1 as a potential target to boost antiviral immune response.